Dietary betaine prevents obesity through gut microbiota-drived microRNA-378a family. (1st January 2021) - Du, Jingjing; Zhang, Peiwen; Luo, Jiang; Shen, Linyuan; Zhang, Shunhua; Gu, Hao; He, Jin; Wang, Linghui; Zhao, Xue; Gan, Mailing; Yang, Liu; Niu, Lili; et al.
ABSTRACT: Betaine is a natural compound present in commonly consumed foods and may have a potential role in the regulation of glucose and lipids metabolism. However, the underlying molecular mechanism of its action remains largely unknown. Here, we show that supplementation with betaine contributes to improved high-fat diet (HFD)-induced gut microbiota dysbiosis and increases anti-obesity strains such as Akkermansia muciniphila, Lactobacillus, and Bifidobacterium . In mice lacking gut microbiota, the functional role of betaine in preventing HFD-induced obesity, metabolic syndrome, and inactivation of brown adipose tissues are significantly reduced. Akkermansia muciniphila is an important regulator of betaine in improving microbiome ecology and increasing strains that produce short-chain fatty acids (SCFAs). Increasing two main members of SCFAs including acetate and butyrate can significantly regulate the levels of DNA methylation at host miR-378a promoter, thus preventing the development of obesity and glucose intolerance. However, these beneficial effects are partially abolished by Yin yang (YY1), a common target gene of the miR-378a family. Taken together, our findings demonstrate that betaine can improve obesity and associated MS via the gut microbiota-derived miR-378a/YY1 regulatory axis, and reveal a novel mechanism by which gut microbiota improve host health.